Copy-number variants in the contactin-5 gene are a potential risk factor for autism spectrum disorder - Schmilovich, Zoe; Huguet, Guillaume; He, Qin; Musa-Johnson, Amélie; Douard, Elise; Loum, Mor Absa; Liao, Calwing; Ross, Jay P.; Dionne-Laporte, Alexandre; Spiegelman, Dan; Jean-Louis, Martineau; Saci, Zohra; et al. (Research in autism spectrum disorders, 2022)
Background - Contactin-5 (CNTN5) is a candidate risk gene for autism spectrum disorder (ASD). Previous attempts to associate CNTN5 CNVs with ASD-susceptibility were limited by insufficient statistical power. Here, we aim to clarify the putative association between CNTN5 CNVs and ASD-risk using large-scale case-control analyses. - Method - A CNTN5 CNV, shared by four brothers in a multiplex family with ASD, was initially identified. We calculated the prevalence and transmission of CNTN5 CNVs in cases across five ASD cohorts (n=15,784). Second, we compared the prevalence of CNTN5 CNVs in cases to their unaffected siblings (n=4,996). Third, we assessed the enrichment of CNTN5 CNVs in cases to extrafamilial controls across three cohorts (n=24,886) and the UK Biobank (n = 459,862). Finally, we evaluated the clinical impact of CNTN5 CNVs in a broad neurodevelopmental disorder cohort and the DECIPHER database. - Results - Most (96.7%) CNTN5 CNV deletions (0.193%) and duplications (0.03%) in cases were inherited by a parent that transmitted the variant to their affected and unaffected children at the same rate. We identified a significant enrichment of intronic CNTN5 CNV deletions in cases compared to extrafamilial controls (0.178% versus 0.019%; p-value=1.68E-05; OR:8.51; 95%CI=[2.58-44.21]). There was no difference in CNTN5 CNV enrichment between cases and individuals with NDDs. - Conclusions - Intronic CNTN5 CNV deletions are rare, inherited, and intermediate effect size ASD-susceptibility variants that may also confer risk for other neuropsychiatric disorders. We offer a framework to characterize candidate variants that may not be detected through small-scale approaches to implicate intermediate effect size variants in the etiology of ASD.
Online verfügbar: 20 October 2022, Artikelversion: 20 October 2022
Gesehen am 25.07.2023